Training of education experts in Ukraine - Ognevyuk Viktor; Sysoieva Svitlana (Borys Grinchenko Kyiv Metropolitan University, 2015)
This article presents training of education experts in Ukraine through the providing interdisciplinary program; analysis of experts training in the field of education abroad. It determines the notion of «expert» and «expertise» their content for peer education activities. Here is shown the results of a pilot study conducted in Ukraine to determine the educational community views on the necessity to provide special experts' training in the field of education and to determine their place in the Ukrainian system of education. Here is discussed the content of the first in Ukraine interdisciplinary Master's program «Expert activities in providing quality of education».